1964
DOI: 10.1079/bjn19640038
|View full text |Cite
|
Sign up to set email alerts
|

The food purchases of elderly women living alone: a statistical inconsistency and its investigation

Abstract: Budgetary surveys of the quantities of food obtained for consumption by whole households cannot by their very nature give direct information about the diets of individuals. This may not matter to economists; to nutritionists it is a most serious limitation. There is only one small but important group of households, those consisting of one person, for whom it is prima facie possible to use budgetary records to assess actual food consumption. Some early National Food Survey records indicated that such assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

1981
1981
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
(1 reference statement)
0
6
1
Order By: Relevance
“…food intake falls [3] and nutritional status has been reported by many workers as being low [3][4][5], Despite this, the 'average' elderly person is reported to be 20% above the suggested weight for height [6] and though this could be a result of an inadequate reduction in energy intake, the available evidence does not support this.…”
Section: Introductioncontrasting
confidence: 41%
“…food intake falls [3] and nutritional status has been reported by many workers as being low [3][4][5], Despite this, the 'average' elderly person is reported to be 20% above the suggested weight for height [6] and though this could be a result of an inadequate reduction in energy intake, the available evidence does not support this.…”
Section: Introductioncontrasting
confidence: 41%
“…While such data are readily collected from large numbers of households and deal with actual purchases and expenditure (the substance of any budget), they typically omit food and drink purchased and eaten away from home, such as canteen or school meals, sweets, soft drinks and alcoholic beverages. Also, there is evidence that food purchasing surveys distort the usual pattern of purchases and consumption, either by encouraging the use of stored food in surveys in which a larder inventory is included (Hollingsworth & Baines,196l), or by promoting 'over-purchasing' of foodstuffs over and above actual consumption in surveys without a larder inventory [Platt et al, 1964;Nelson et al, 1985). There is also the problem of estimating the nutrient content of food purchases when trying to assess dietary adequacy.…”
Section: Introductionmentioning
confidence: 99%
“…Overpurchasing. The very act of being surveyed may have stimulated extra purchasing during the week, as was shown to occur in NFS households containing elderly women living alone (Platt et al 1964). Purchases made in bulk or stimulated by special offers and discounts plus the need to avoid running out of non-perishables may mean that a surplus is often purchased for the larder.…”
Section: Sample Co-operationmentioning
confidence: 99%
“…Validation studies showed little change in the energy value of purchases immediately before and after larder inventories were discontinued, with one exception: the energy content of purchases of single female old-age-pensioner (OAP) households was 2.09 MJ (500 kcal)/person per d greater after inventories ended (Platt et al 1964). Platt et al (1964) also examined analyses by Baines & Hollingsworth (1955) and observed that in this type of household, between April 1953 andMarch 1954, 'the energy value of food obtained for 374…”
mentioning
confidence: 99%
See 1 more Smart Citation